2018
DOI: 10.1111/ecc.12908
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported quality of life and hope in phase-I trial participants: An observational prospective cohort study

Abstract: For advanced cancer patients deliberating early clinical trial participation, adequate information about expected effect on quality of life (HRQoL) and hope, may support decision making. The aim was to assess the potential relation of HRQoL to eligibility for phase-I trial participation, and to observe the variations in patient-reported outcomes. Patients completed questionnaires at preconsent (n = 124), baseline (n = 96), and after first evaluation of a phase-I trial (n = 76). The Mann-Whitney U test was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Physicians and nurses found that a most difficult challenge was end-of-life patients eager to participate in all kinds of cutting-edge drug trials, often with an unrealistic hope for possible gain. The patients sometimes had high expectation concerning benefits [17][18][19][20][21][22], or believed the trials were miracles waiting to happen [23]. Though questionable, many physicians found it important to uphold hope and to support a belief in clinical trials because it can benefit patients and relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians and nurses found that a most difficult challenge was end-of-life patients eager to participate in all kinds of cutting-edge drug trials, often with an unrealistic hope for possible gain. The patients sometimes had high expectation concerning benefits [17][18][19][20][21][22], or believed the trials were miracles waiting to happen [23]. Though questionable, many physicians found it important to uphold hope and to support a belief in clinical trials because it can benefit patients and relatives.…”
Section: Introductionmentioning
confidence: 99%